EFEK UMUR PEMANGKASAN INDIGOFERA (Indigofera zollingeriana) PADA MUSIM KEMARAU TERHADAP KANDUNGAN NETRAL DETERGEN FIBER DAN ACID DETERGEN FIBER - Syahrio Tantalo; Liman Liman; Farida Fathul (JURNAL ILMIAH PETERNAKAN TERPADU, 2019)
This research aims to determine the effect of harvest age Indigofera zollingeriana in dry season on the content of Neutral Detergent Fiber (NDF) and Acid Detergent Fiber (ADF). This research used a completely randomized design with four treatments and three replications. The treatment consisted of harvest age at 40 days, harvest age at 55 days, harvest age at 70 days, and harvest age at 85 days. Data were analyzed using Variance Analysis and post-hoc test of Least Significance Different (LSD). The parameters consisted of NDF and ADF. The results of this research indicate that Indigofera zollingeriana which was harvested at 55 days has the highest NDF content (81.61%) and has significantly different (P <0.01) than the NDF content at harvest age of 40 days (70.93%), harvest age 70 days (68.80%), and at harvest age 85 days (67.23%). In addition, Indigofera zollingeriana that was harvested at 55 days has ADF content (56.68%) and at 70 days of harvest had ADF content (54.24%) that was significantly different (P <0.01) compared to ADF content at harvest age of 40 days by 48.35% and the harvest age of  85 days bay 49,41%.  It was concluded that Indigofera zollingeriana at the harvest age of 55 days in the dry season was the best harvest age with its NDF content of 81.61% and the ADF content of 56.68%. Therefore, it is recommended to plant Indigofera zollingeriana in the dry season, and it should be harvested at the harvest age of 55 days. Keywords:   Acid Detergent Fiber, Dry season, Harvest Age, Indigofera zollingeriana, Neutral Detergent  Fiber